Semiconductor Devices Theory and Application - Fiore, James M. (Open textbook library., 2018)
The goal of this text, as its name implies, is to allow the reader to become proficient in the analysis and design of circuits utilizing discrete semiconductor devices. It progresses from basic diodes through bipolar and field effect transistors. The text is intended for use in a first or second year course on semiconductors at the Associate or Baccalaureate level. In order to make effective use of this text, students should have already taken coursework in basic DC and AC circuits, and have a solid background in algebra and trigonometry along with exposure to phasors. Calculus is used in certain sections of the text but for the most part it is used for equation derivations and proofs, and is kept to a minimum. For students without a calculus background these sections may be skipped without a loss of continuity. There is also a lab manual for this textbook.